Where are we in the implementation of tissue-specific epigenetic clocks? - Sala, Claudia; Di Lena, Pietro; Fernandes Durso, Danielle; Faria do Valle, Italo; Bacalini, Maria Giulia; Dall’Olio, Daniele; Franceschi, Claudio; Castellani, Gastone; Garagnani, Paolo; Nardini, Christine (Frontiers in Bioinformatics, 2024)
DNA methylation clocks presents advantageous characteristics with respect to the ambitious goal of identifying very early markers of disease, based on the concept that accelerated ageing is a reliable predictor in this sense. Such tools, being epigenomic based, are expected to be conditioned by sex and tissue specificities, and this work is about quantifying this dependency as well as that from the regression model and the size of the training set. Our quantitative results indicate that, while the penalization strategy does not statistically significantly affect the clock's performance, training the models with bigger sample sizes -unsurprisingly-improves the predictions. Moreover, sex does not appear to condition clocks performances and tissuespecific clocks appear to perform better than generic blood clocks. Finally, when considering all trained clocks, we identified a subset of genes that, to the best of our knowledge, have not been presented yet and might deserve further investigation: CPT1A, MMP15, SHROOM3, SLIT3, and SLC9A3. These factual starting points can be useful for the future medical translation of clocks and in particular in the debate between multi-tissue clocks, generally trained on a large majority of blood samples, and tissue-specific clocks.